BMI and Allostatic Load Are Directly Associated with Longitudinal Increase in Plasma Neurofilament Light among Urban Middle-Aged Adults. Issue 2 (29th October 2021) - Beydoun, May A; Noren Hooten, Nicole; Maldonado, Ana I; Beydoun, Hind A; Weiss, Jordan; Evans, Michele K; Zonderman, Alan B
ABSTRACT: Background: Plasma neurofilament light chain (NfL) is a novel biomarker for age-related neurodegenerative disease. We tested whether NfL may be linked to cardiometabolic risk factors, including BMI, the allostatic load (AL) total score (ALtotal ), and related AL continuous components (ALcomp ). We also tested whether these relations may differ by sex or by race. Methods: We used data from the HANDLS (Healthy Aging in Neighborhoods of Diversity across the Life Span) study [ n = 608, age at visit 1 (v1 : 2004–2009): 30–66 y, 42% male, 58% African American] to investigate associations of initial cardiometabolic risk factors and time-dependent plasma NfL concentrations over 3 visits (2004–2017; mean ± SD follow-up time: 7.72 ± 1.28 y), with outcomes being NfLv1 and annualized change in NfL (δNfL). We used mixed-effects linear regression and structural equations modeling (SM). Results: BMI was associated with lower initial (γ01 = −0.014 ± 0.002, P < 0.001) but faster increase in plasma NfL over time (γ11 = +0.0012 ± 0.0003, P < 0.001), a pattern replicated for ALtotal . High-sensitivity C-reactive protein (hsCRP), serum total cholesterol, and resting heart rate at v1 were linked with faster plasma NfL increase over time, overall, while being uncorrelated with NfLv1 (e.g., hsCRP × Time, full model: γ11 = +0.004 ± 0.002, P = 0.015). In SM analyses, BMI's association with δNfL was significantly mediated through ALtotal among women [total effect (TE) = +0.0014 ± 0.00038, P < 0.001; indirect effect = +0.00042 ± 0.00019, P = 0.025; mediation proportion = 30%], with only a direct effect (DE) detected among African American adults (TE = +0.0011 ± 0.0004, P = 0.015; DE = +0.0010 ± 0.00048, P = 0.034). The positive associations between ALtotal /BMI and δNfL were mediated through increased glycated hemoglobin (HbA1c) concentrations, overall. Conclusions: Cardiometabolic risk factors, particularly elevated HbA1c, should be screened and targeted for neurodegenerative disease, pending comparable longitudinal studies. Other studies examining the clinical utility of plasma NfL as a neurodegeneration marker should account for confounding effects of BMI and AL.